THE CREATIVE POWER OF PAUL GERTRUDE IN D.H. LAWRENCE'S SONS AND LOVERS : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SETYANGGORO , BINTANG (2006)
The study is to reveal how Paul's creative power influences his personality. The objective of the study is to analyze the novel based on the structural analysis and the individual psychological analysis. The study is a qualitative study. The object of the study is D.H Lawrence Sons and Lovers published in Great Britain in 1913 by Reed International Books Limited London. The data sources are divided into two, namely primary data source and secondary data source. The secondary data source are the other sources related to the analysis such as the authors biography, essay, and other literary work, which are related to this study. The method of data collection is library research. The technique of data analysis is descriptive analysis. The result of this study is as follows: Firstly, the structural elements of the novel present a unity. It appears in the exposition, complication, climax, and resolution of the story. Secondly, the psychological analysis shows that mother's death has effect to person's inferiority feeling and fictional finalism has pushed him to do some efforts to attain the superiority. Basically Paul is a good man. He really loves his mother. Paul thinks that his mother is the most important thing in his life. They are inseparable. He confides everything in her, works and paints to please her. However, he finally killed his mother because he did not want to saw his mother suffer because of tumor sick. Finally, the psychological analysis shows that the human factor especially mother will change the person's character.